Aging and Long Term Care Systems : A Review of Finance and Governance Arrangements in Europe, North America and Asia-Pacific - Joshua, Laurie (World Bank, Washington, DC, 2017)
Population aging is a global issue that is either affecting or will soon affect virtually every country around the world. With large numbers of older people experiencing significant losses of intrinsic capacity, leading a dignified and meaningful life is often only possible with the care and support of others. Long-term care (LTC) has therefore become one of the most rapidly developing policy areas in OECD countries, where significant institutional change and innovation have taken place over the last two decades. Governance and finance arrangements for the delivery of LTC differ between countries. LTC in the Netherlands, Germany, Japan, The Republic of Korea, the Scandinavian countries (Sweden, Denmark and Finland), England, the United States, France1 were selected to cover differences between systems. However, across the different systems debates about intergenerational and state responsibilities are increasing evident. The paper delivers an up-to date assessment of design parameters and captures the measures being taken to build financial sustainability into LTC policy and program reforms. Rapid population aging in low and middle income countries (LMICs) will inevitably generate an increased demand for long-term care (LTC) services. Research and practical experience from high income countries – and the very diverse patterns of LTC in terms of funding mechanism, the balance of formal and informal services, the degree of state participation, and the overall level of provision – hold important lessons.